HIGH-PERFORMANCE VECTOR CONTROL STRATEGY FOR MULTILEVEL INVERTER FED INDUCTION MOTOR - Tuncer, Servet (Gazi Univ, Fac Engineering Architecture, 2015)
This paper presents a high-performance vector control strategy for Multilevel Inverter (MLI) fed induction motor drive system. In the proposed drive system, an adaptive and online trained sugeno type neuro-fuzzy speed controller is used to improve the speed tracking performance. The generation of Pulse Width Modulation (PWM) patterns for multilevel inverter is obtained using space vector PWM algorithm. The complete drive system is implemented in real time using DS1104 controller card. Using the experimental setup, the performance of the proposed drive system is tested under different speed commands, mechanical parameter variations and load disturbances. The experimental results show that control performance of the proposed drive system is satisfactory.
Keywords: Space vector PWM; neuro-fuzzy controller; indirect vector control; multilevel inverter and induction motor